Coloniality of Student Support Services: Young People’s Lived Experiences at the Intersection of Race, Disability and Mental Distress - Kurki, Tuuli; Niemi, Anna-Maija (Cappelen Damm Akademisk NOASP, 2025)
In this article, we examine the lived experiences of young people who receive student support services through the lenses of coloniality and intersectionality. Our focus is on student support services within the Finnish education system, encompassing support for schoolwork and learning, and mental health and well-being. Drawing on two research projects – a multi-sited ethnographic study and an ethnography-based life-historical study – we shed light on the lived experiences of four young people as they navigate school and its support system. We apply the theoretical concepts of coloniality and intersectionality to empirically analyse the racialising, disabling and mentally distressing practices encountered by young people in their interactions with student support services. Implicit in the lived experiences of all four individuals is the absence of intersectional understanding of the complexities of young people’s lives, leading to feelings of perplexity and neglect in support. However, these experiences also give rise to subtle yet powerful forms of resistance that envision a decolonised future, also within student support services.